Inherited institutions: Cooperation in the light of democratic legitimacy - Pascal Langenbach; Franziska Tausch (Max Planck Institute for Research on Collective Goods, 2017)
We experimentally investigate whether the procedural history of a sanctioning institution affects cooperation in a social dilemma. Subjects inherit the institutional setting from a previous generation of subjects who either decided on the implementation of the institution democratically by majority vote or were exogenously assigned a setting. In order to isolate the impact of the voting procedure, no information about the cooperation history is provided. In line with existing empirical evidence, we observe that in the starting generation cooperation is higher (lower) with a democratically chosen (rejected) institution, as compared to the corresponding, randomly imposed setting. In the second generation, the procedural history only partly affects cooperation. While there is no positive democracy effect when the institution is implemented, the vote-based rejection of the institution negatively affects cooperation in the second generation. The effect size is similar to that in the first generation.
Keywords: C92; D02; D71; D72; H41; 330; Endogeneity; Voting; Institutions; Social dilemma; Public good; Inherited rules